Public Participation As An Instrument Of Performance Of Eu-Funded Cross-Border Projects - Pozarnik, Matej; Sotlar, Vesna (European Scientific Journal, ESJ, 2016)
The objective of the European territorial cooperation programme INTERREG has been financing joint projects of cross-border areas ever since 1990. Since many projects, financed in the past, did not provide longterm effects, the European Union decided to introduce the “result-driven approach” to these programmes. The realization of results will be consequently monitored during the project financing and after completion of selected projects. If one wishes to ensure sustainability also after the end of financing, the public and target groups must be actively involved in preparation and implementation of projects from the very beginning. The purpose of this paper is to present possibilities of public participation in different phases of the project. A comprehensive model of public participation was developed on the basis of research, involving the public into the sustainable life-cycle of a cross-border project.